Students’ Responses Towards Drama Performance Course Process - Eka Margianti Sagimin (UICELL, 2018)
This study aims at investigating and analyzing students’ responses towards Drama Performance Course learning process by surveying sixth (6th) semester students of English Department, Universitas Pamulang. The purpose of this study is to get a general description of students’ responses, especially from the students’ point of view who are directly involved in the process. In addition, this study is also expected to provide benefits as an evaluation material for teaching literature and as a reference for continuing practicum-based courses namely Drama Performance. Qualitative research design is employed concerning to the learning process of Drama Performance Course. The data were collected by using observation, questionnaire and documentation. As many as 94 respondents in this study were taken from seven classes of the sixth semester students. Based on the results of data analysis, it can be concluded that the response of students towards the learning process were positive which taken from 5 categories, namely: the response to the Drama Performance course, the students’ response to the learning process, the process of role deepening, increasing speaking skills, students interaction and the role of the lecturer. Indeed, the students’ creativity in drama production, as well as their performances and staging actions were also ran successful.